2009
DOI: 10.2355/isijinternational.49.312
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Dislocation Structure and Fatigue Crack Behavior in Fe–Si Alloys during Cyclic Bending Test

Abstract: Fig. 14. TEM micrographs of Ti-IF3(1 % Si) tested under a high stress amplitude showing development of the periodically arranged dislocation wall structure near the top surface (sϭ380.9 MPa, Nϭ8 500).proximately 0.5 mm in the Si-bearing steels. Concerning the interaction between dislocations and grain boundaries during the cyclic test, detailed studies on Cu polycrystal, 17,23) Cu bicrystal 24) and Al polycrystal 25) were carried out taking into account the grain boundary characteristics. Winter et al. 17) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 23 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…It has been reported that the addition of Si lowered stacking fault energy to make it more difficult for dislocations to cross slip in Fe-Si alloys. 17) Moreover, the increasing ds/de value by Si addition in interstitial free (IF) steels was confirmed due to the difficult formation of dislocation cell structure. 18,19) Thus, the solute Si atom in ferrite influenced its dislocation interactions during deformation so as to increase the strain-hardening rate, and therefore, total and uniform elongations at a given strength level.…”
Section: Effect Of Si On Tensile Propertiesmentioning
confidence: 91%
“…It has been reported that the addition of Si lowered stacking fault energy to make it more difficult for dislocations to cross slip in Fe-Si alloys. 17) Moreover, the increasing ds/de value by Si addition in interstitial free (IF) steels was confirmed due to the difficult formation of dislocation cell structure. 18,19) Thus, the solute Si atom in ferrite influenced its dislocation interactions during deformation so as to increase the strain-hardening rate, and therefore, total and uniform elongations at a given strength level.…”
Section: Effect Of Si On Tensile Propertiesmentioning
confidence: 91%
“…A large-scale 3D dislocation dynamics simulation 57 suggests a cell structure formation due to the easy cross slip, which is also observed as a cell-like pattern in the plane perpendicular to the Burgers vector. 55 On the other hand, in the case of Fe-Si alloy, since the cross slip becomes difficult, a dislocation stuck to other immobile dislocations leads to work hardening. Eventually, dislocations may form the vein structure, which is usually observed in dilute Fe-Si alloys as mentioned above.…”
Section: Dislocationmentioning
confidence: 99%
“…However, the framework does not answer the question why the most preferable slip system often changes by the addition of a solute atom. 48,55 In fact, in the Fe-Si dilute alloys, the {110}<111> slip system becomes the most preferable, 48,55 while the {110}<111> and {112}<111> slip systems are equally preferable in pure Fe. To answer this question, we constructed a spatiotemporal coarse-grained kMC 56 based on the energy barriers of kink nucleation and migration with and without solute Si.…”
Section: Dislocationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the stator of driving engine consists of segments cut out from the sheets of grain nonoriented electrotechnical steel, the rotor is usually made by casting or sintering of powder materials, which considerably increases already high production costs. Also the resistance of these sintered materials toward dynamic fatigue is not sufficient [4,5]. Nowadays the attention is focused on the development of high-strength electrotechnical steels exhibiting the combination of demanding mechanical and good electro-magnetic properties.…”
Section: Introductionmentioning
confidence: 99%